THE EFFORTS OF ISLAMIC EDUCATIONAL INSTITUTIONS IN OVERCOMING BULLYING; ROLES, FUNCTIONS AND REALITIES THAT OCCUR - Itaanis Tianah; Sri Ira Suharwati; Shinta Oktafiana; Sahrul Romadhan; Faraniena Yunaeni Risdiana; Deddy Wahyudi; Atin Ismatus Zehro (SOSIOEDUKASI, 2026)
Educational institutions are the second place in socializing as well as shaping the character and behavior of students. Including preventing students from bullying. Educational Institutions have the responsibility to prevent bullying through various efforts that can be made by educational institutions. This article discusses the efforts of the Muhammadiyah Educational Institute in instilling religious values and making other efforts in preventing bullying. The efforts made by the Muhammadiyah Education Institution are through the recitation of books such as the interpretation of the Hadith and the Qur'an, manners and morals through habituation in schools. Habituation in worship, especially dhuha worship and through lectures seven minutes after dhuha. Included in the lesson plan in the subjects of Citizenship Education, Islamic Religious Education, Sociology, Indonesian. Muhammadiyah Educational Institutions also carry out additional activities such as the Youth Information and Counseling Center (PIK-R) which is held every Saturday but this is done by high schools, while for junior high schools there has been no special effort to only socialize about the dangers of bullying. In addition, it was conveyed at every ceremony about the importance of respecting each other and not bullying their friends. However, the efforts made by the Muhammadiyah Educational Institution have not been effective in preventing bullying because there is still verbal bullying as much as 52%, in the form of body shaming, calling with the call of parents, mocking with the call of stupidity of bego, calling by the name of an animal, and calling by the name of a ghost. Physical bullying as much as 34% such as kicking, strangling, and hitting, some initially joking developed into fights. and includes a 14% relational exclusion of spreading rumors so that friends stay away and carry out demolitions. This reality shows that educational institutions, even if they are based on religious values, need to make more intense efforts in overcoming and preventing bullying. This research uses qualitative research with a case study approach and is analyzed from a sociological perspective.